2012
DOI: 10.1021/nn202556b
|View full text |Cite
|
Sign up to set email alerts
|

Templated Synthesis of Amphiphilic Nanoparticles at the Liquid–Liquid Interface

Abstract: A simple and reliable method is described to produce inorganic nanoparticles functionalized asymmetrically with domains of hydrophobic and hydrophilic ligands on their respective hemispheres.These amphiphilic, Janus-type particles form spontaneously by a thermodynamically controlled process, in which the particle cores and two competing ligands assemble at the interface between two immiscible liquids to reduce the interfacial energy. The asymmetric surface chemistry resulting from this process was confirmed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 43 publications
4
92
0
Order By: Relevance
“…In both cases, the liquid vaporizes on cooling, but the gas phase is composed by (weakly interacting) aggregates in which particles are ordered in configurations of very low energy but also very low entropy, changing the slope of the binodal at low T. In the Janus case, the gas is indeed formed by micelles and vesicles, 47 while in the 2A9B case, the gas is composed of rings. 51 Thus, the physics that stabilizes the gas phase at low T allows the spinodal to rise back to positive P. Finally, we note that both models might be realized experimentally in the near future, [61][62][63][64] allowing for an experimental confirmation of the numerical and theoretical results reported here. The peculiar properties of these systems, while being somewhat different from those of water (for which there is no evidence of a lower gas-liquid critical point and the binodal is positively sloped), can shed light on the thermodynamics of anomalous fluids.…”
supporting
confidence: 72%
“…In both cases, the liquid vaporizes on cooling, but the gas phase is composed by (weakly interacting) aggregates in which particles are ordered in configurations of very low energy but also very low entropy, changing the slope of the binodal at low T. In the Janus case, the gas is indeed formed by micelles and vesicles, 47 while in the 2A9B case, the gas is composed of rings. 51 Thus, the physics that stabilizes the gas phase at low T allows the spinodal to rise back to positive P. Finally, we note that both models might be realized experimentally in the near future, [61][62][63][64] allowing for an experimental confirmation of the numerical and theoretical results reported here. The peculiar properties of these systems, while being somewhat different from those of water (for which there is no evidence of a lower gas-liquid critical point and the binodal is positively sloped), can shed light on the thermodynamics of anomalous fluids.…”
supporting
confidence: 72%
“…For example, the adsorption of colloids, nanoparticles, polymers, or proteins at fluid-fluid interfaces are highly relevant for industrial products (food, 1 Pickering Emulsion, 2-4 particle synthesis, 5 cosmetics, paints, etc.) and vital for engineering processes (washing, coating, water purification, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins differentially adsorb and denature at the oil-water interface depending on properties such as size, surface hydrophobicity, and surface charge (Li et al, 2012; Keerati-u-rai et al, 2012, Tubio et al, 2004). Other investigators have shown the utility of this molecular self-assembly at oil-water interfaces to specifically control aggregation of droplets in emulsion (Hadorn and Boenzli, 2012) and to create amphiphilic nanoparticles (Andala et al, 2012). …”
Section: Introductionmentioning
confidence: 99%